Mimesis: Some reflections on bodhicitta verses in the second chapter of the Guhyasamājatantra - Korobov, Vladimir (Acta Orientalia Vilnensia, 2010)
Vilnius University Although the ultimate bodhicitta functions within a non-dual model of cognition where oppositions (good and evil, pure and impure, saṃsāra–nirvāṇa, etc.) do not exist, it is traditionally considered to be the wisdom cognising emptiness. In this paper I will try to explore the cognitive nature of the ultimate bodhicitta to answer the question ‘What kind of cognition is the cognising of emptiness?’ In the paper I also will make an attempt to describe the basics of ambivalent Tantric ethics in terms of the phenomenological category of imitation or mimesis. Verses on the ultimate bodhicitta in the second chapter of the Guhyasamājatantra are a subject of commentaries written by various Tibetan and Indian authors. The paper is supplemented with a translation of Bodhicittabhāvanā written by Ācārya Kamalaśīla. This short text is a commentary on verses proclaimed by Tathagāgata Vairocana in the second chapter of Guhyasamājatantra.